Desain Inverter Satu Fasa 12V DC ke 220V AC Menggunakan Rangkaian H-Bridge MOSFET - Andhika Giyantara; Risky Susanto Tjiang; Subchan Subchan (LPPM ITK, 2019)
Inverter is an electronic circuit that convert electric voltage with direct current (DC) to alternating current (AC). One of the commonly used inverter configuration is H-Bridge circuit. Inverter with H-Bridge circuit does not need voltage-balanced diode or capacitor to operate and can be cascaded to obtain multilevel output voltage. H-Bridge circuit works by adjusting the combination of switches that were enabled. One of the commonly used switches is Metal Oxide Semiconductor Field Effect Transistor (MOSFET). The advantages of MOSFET as switching components are its fast switching speed and it did not cause current tail. Therefore, the writing of this paper aims to design a 12V DC to 220V AC 50Hz single-phase inverter with H-Bridge MOSFET circuit. The design stage begins with determining the specifications of the inverter, creating a block diagram of the inverter, determining the required components, and calculating the required parameters of the inverter. The designed inverter is simulated using Proteus 8.4 software. Simulation results are in accordance with the desired specification.